Prognostic value of blastocyst grade after frozen euploid embryo transfer in patients with recurrent pregnancy loss - Gayathree Murugappan, M.D; Julia G. Kim, M.D; Jonathan D. Kort, M.D; Brent M. Hanson, M.D; Shelby A. Neal, M.D; Ashley W. Tiegs, M.D; Emily K. Osman, M.D; Richard T. Scott, M.D; Ruth B. Lathi, M.D (Elsevier, 2020)
Objective: To determine whether trophectoderm (TE) grade or inner cell mass (ICM) grade have predictive value after euploid frozen embryo transfer (euFET) among recurrent pregnancy loss (RPL) patients. Design: Retrospective cohort study. Setting: Single fertility center. Patient(s): Women with ≥2 prior pregnancy losses with ≥1 euploid embryo for transfer undergoing preimplantation genetic testing for aneuploidy. Intervention(s): Intracytoplasmic sperm injection, TE biopsy, blastocyst grading and vitrification, and single euFET, with first transfer outcome recorded. Main Outcome Measure(s): Live birth and clinical miscarriage rates. Result(s): The study included 660 euFET cycles. In a binomial logistic regression analysis accounting for age, body mass index, antimüllerian hormone level, and day of blastocyst biopsy, or ICM grade C was not significantly associated with odds of live birth, miscarriage, or biochemical pregnancy loss. TE grade C was significantly associated with odds of live birth and was not associated with odds of miscarriage or biochemical pregnancy loss. Blastocyst grade CC had significantly lower live birth rate compared with all other blastocyst grades. Conclusion(s): Embryo grade CC and TE grade C are associated with decreased odds of live birth after euFET in RPL patients. Embryo grade is not associated with odds of clinical miscarriage in this cohort of RPL patients, suggesting that additional embryonic or uterine factors may influence the risk of pregnancy loss.